Natural products targeting glycolytic signaling pathways-an updated review on anti-cancer therapy - Cui, Yuting; Li, Chuang; Sang, Feng; Cao, Weiling; Qin, Zhuo; Zhang, Peng (Frontiers in Pharmacology, 2022)
Glycolysis is a complex metabolic process that occurs to convert glucose into pyruvate to produce energy for living cells. Normal cells oxidized pyruvate into adenosine triphosphate and carbon dioxide in the presence of oxygen in mitochondria while cancer cells preferentially metabolize pyruvate to lactate even in the presence of oxygen in order to maintain a slightly acidic micro-environment of PH 6.5 and 6.9, which is beneficial for cancer cell growth and metastasis. Therefore targeting glycolytic signaling pathways provided new strategy for anti-cancer therapy. Natural products are important sources for the treatment of diseases with a variety of pharmacologic activities. Accumulated studies suggested that natural products exhibited remarkable anti-cancer properties both in vitro and in vivo. Plenty of studies suggested natural products like flavonoids, terpenoids and quinones played anti-cancer properties via inhibiting glucose metabolism targets in glycolytic pathways. This study provided an updated overview of natural products controlling glycolytic pathways, which also provide insight into druggable mediators discovery targeting cancer glucose metabolism.